2021
DOI: 10.18553/jmcp.2021.27.10.1482
|View full text |Cite
|
Sign up to set email alerts
|

Validation of EHR medication fill data obtained through electronic linkage with pharmacies

Abstract: BACKGROUND: Recent linkages between electronic health records (EHRs) and pharmacy data hold opportunity for up-to-date assessment of medication adherence at the point of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 19 publications
(22 reference statements)
0
26
0
Order By: Relevance
“… 4 Pharmacy fill data, particularly PDC, are considered to be the most practical and inexpensive technique and are suitable for use in large population studies. 19 However, PDC may not be readily available for the general practitioner, whereas CAT is used increasingly in clinical practice. Pharmacy fill records may not reflect adherence adequately if prescription data are not captured from all potential sources or patients do not take the dispensed medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Pharmacy fill data, particularly PDC, are considered to be the most practical and inexpensive technique and are suitable for use in large population studies. 19 However, PDC may not be readily available for the general practitioner, whereas CAT is used increasingly in clinical practice. Pharmacy fill records may not reflect adherence adequately if prescription data are not captured from all potential sources or patients do not take the dispensed medications.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a recent analysis showed that pharmacy fill data available in the electronic heath record overestimated adherence when compared with insurance claims data. 19 CAT is another technique increasingly used in the United States and many other countries to assess medication adherence as it is easy to obtain and highly sensitive. 10 , 11 However, white coat adherence (taking the pills only when tested) may occur if patients are aware of the tests, which limits accuracy of biochemical adherence testing as the gold standard test.…”
Section: Discussionmentioning
confidence: 99%
“…The health system’s EHR provided demographic information, laboratory test results, weight, blood pressure, and health care use. Prescription drug orders were recorded, and whether they were dispensed at major pharmacy chains was observed using Surescripts . For patients enrolled in the health system’s insurance plan, paid claims were available.…”
Section: Methodsmentioning
confidence: 99%
“…Prescription drug orders were recorded, and whether they were dispensed at major pharmacy chains was observed using Surescripts. 33 For patients enrolled in the health system's insurance plan, paid claims were available.…”
Section: Datamentioning
confidence: 99%
“…Two data sources were used to compute PDC: (1) pharmacy fill information (Surescripts) and (2) prescription information (EHR). As previously described by our group, this EHR-linked data set was comprehensive and contained more prescription fill information than insurance claims data. PDC was measured over 6 months from time of prescription order and averaged across GDMT categories if more than 1 GDMT was prescribed, as previously described .…”
Section: Methodsmentioning
confidence: 99%